(untitled) (Modern education and development, 2025)
This study explores the impact of personal emotional journal writing on improving English language fluency among adult learners. As emotional expression and language use are closely interconnected, keeping a regular journal in English allows learners to practice language skills in a meaningful and personalized context. The paper examines how writing about daily emotions and experiences increases vocabulary usage, sentence complexity, and overall fluency. It also highlights how such reflective writing boosts learners’ motivation, self-awareness, and confidence in using English, especially in low-anxiety, private settings. Drawing on qualitative data from classroom interventions and learner reflections, the study concludes that emotional journaling is an effective, low-cost, and learner-centered strategy for enhancing fluency, particularly in adult education and ESL contexts.